(untitled) (Al-Academy, 2015)
Constitute the relationship between the director and actor mainstay chock done to show art in film and television , both of which occupy what a big role in the mission accomplishment . The leadership of the director of the artwork in various joints require two features two important ( creativity and administration ) , The capabilities director of creative serves as an added intellectual and aesthetic saturated sensation that leaves its impact on all the technical elements involved in done. Either trait administration and leadership it is what requires multiple skills in dealing on according to technical standards and moral and humanitarian allow the transfer of ideas , concepts and visions to those elements to embody and implement the kinetics of the film or series in the snapshot and the scene and building the picture as a whole , and this building is a role actor of great importance in the creation and innovation, and the embodiment of data scene representative including blowing Take the idea and merits of event that requires an atmosphere dominated concord and harmony , cooperation and exchange of views and perceptions The experiments professionalism showed the style of both the roles of director and actor , including the detection of impressions and perceptions about the fact that the work of the director and the actor , which nearly or just the distances between them , and that the privacy of the natural will of all of them, but the artwork in the film and television requires the ability to reach to what extent can the relationship between the director and the actor to work on the completion of the technical work is to achieve the integration of technical and overwhelming success away from the problems that differed two in some details , says Joseph Almond ( when you have a good actor knows what you want , and always looking for things within himself , and knows that you will not make it vulnerable to ridicule , Sawa in the imaging site or on the screen , you can then see unusual things occur ) , This Mikhvv the severity of the intersection between them and what creates the atmosphere predisposing to work the camera if it took filmmaker professional role Kabarlaanadan Representative and the follow-up to do with interest and encouragement , and that the merits of working in film and television produced a series of data which we can detect the nature of the relationship between the director and actor , and that the effect of creating problems existing between them , including: 1 - Convinced the director to choose representatives2 - Dealing with representatives3 - Previous experiences4 - To depart from the text5 - Interventions authority production6 - The nature of the performance